Pengenalan Bahan Kimia Sederhana Melalui Pemanfaatan Limbah Rumah Tangga - Muhammad Arif Firdaus; Mohammad Ilham Fardiansyah; Vina Syofiyatul Ulfa; Farhan Abdurahman; Ananda Rizky Utami; Margaretha Desy Gabriela; Dessy Agustina Sari (Journal of Social Responsibility Projects by Higher Education Forum, 2022)
The community service program complements the tri dharma of higher education. Initiated Badan Koordinasi Kegiatan Mahasiswa Teknik Kimia Indonesia - BKKMTKI region 2 in collaboration with Himatemia (Himpunan Mahasiswa Teknik Kimia) Universitas Singaperbangsa Karawang together with the Pendekar Mengajar and the Nusantara Terdidik Foundation. Projects include: introducing simple chemicals, using used materials to make soap, and teaching Madrasah Ibtidaiyyah students equivalent to Elementary Schools. The community service location is in Cibuyutan Village, Bogor Regency. The method used is a straightforward approach following the focus of the community; the teaching part is carried out by the Pendekar Mengajar community and the Nusantara Terdidik Foundation, while the introduction of chemicals by BKKMTKI and Himatemia Unsika. The parameters of success are reviewed from the functionality and the active participation of children; therefore, the activity was successful. The only impediment to the activity lies in access to the village, which hinders mobility.